The Development of Sustainability Graduate Community (SGC) as a Learning Pathway for Sustainability Education - a Framework for Engineering Programmes in Malaysia Technical Universities Network (MTUN) - Kartina, Johan; Faiz, Mohd Turan (IOP Publishing, 2016)
Environmental and sustainability' is one of the Program Outcome (PO) designated by the Board of Engineers Malaysia (BEM) as one of the accreditation program requirement. However, to-date the implementation of sustainability elements in engineering programme in the technical universities in Malaysia is within individual faculty's curriculum plan and lack of university-level structured learning pathway, which enable all students to have access to an education in sustainability across all disciplines. Sustainability Graduate Community (SGC) is a framework designed to provide a learning pathway in the curriculum of engineering programs to inculcate sustainability education among engineering graduates. This paper aims to study the required attributes in Sustainability Graduate Community (SGC) framework to produce graduates who are not just engineers but also skilful in sustainability competencies using Global Project Management (GPM) P5 Standard for Sustainability. The development of the conceptual framework is to provide a constructive teaching and learning plan for educators and policy makers to work on together in developing the Sustainability Graduates (SG), the new kind of graduates from Malaysia Technical Universities Network (MTUN) in Malaysia who are literate in sustainability practices. The framework also support the call for developing holistic students based on Malaysian Education Blueprint (Higher Education) and address the gap between the statuses of engineering qualification to the expected competencies from industries in Malaysia in particular by achieving the SG attributes outlined in the framework